Political Costs and Earnings Management of Oil Companies During the 1990 Persian Gulf Crisis. - Han, Jerry C. Y.; Wang, Shiing-Wu (The Accounting Review, 1998)
Abstract This study investigates whether firms that expect increases in earnings resulting from sudden product price increases use accounting accruals to reduce earnings and, thus, political sensitivity. Specifically, oil firms' accruals are analyzed in a period of rapid gasoline price increases during the 1990 Persian Gulf crisis. Our results show that oil firms that expected to profit from the crisis used accruals to reduce their reported quarterly earnings during the Gulf crisis. In contrast to previous research, we find that the tendency to release good earnings news early, documented in prior research, is reversed for oil firms during the Gulf crisis. This finding suggests that the benefit of disclosing "good news" (i.e., earnings increases) early may have been outweighed by the political costs associated with timely releases of the information.